Blood biochemical profile in relation to age and reproductive status of Holstein Friesian cattle reared under tropical climate - DHAMI, A J; LAKUM, P D; PATEL, P M; PANCHAL, M T; KAVANI, F S (The Indian Journal of Animal Reproduction, 2005)
This study was planned to evaluate haemoglobin content and certain blood biochemical constituents of HF cattle rearedunder tropical climate in relation to different age groups and physiological status. All 72 female animals ( 6 in each group) were selectedat random from the HF herd according to their age and physiological status, viz., 1-2 weeks, 2-3 months, 5-6 months, 8-9 months, 11-12 months and 17-18 months old and of varied reproductive status, viz., cyclic/early pregnant heifers (22-24 months old), advancedpregnant heifers (30-36 months old), recently calved cows (0 day), cyclic/lactating cows (2 months postpartum), anoestrus cows (5-6 months post-partum) and repeat breeder cows (6-9 months postpartum). Hepariniz.ed venous blood samples were obtained once fromall animals at specified age/status for this study. The mean Hb content of blood varied from 9.00±0.43 to 11.03±0.22 g% (P-dl.01) witha pooled mean of 9.91::t:0.16 g%. Similarly, the mean values of different biochemical constituents, viz., plasma total protein,triglycerides, calcium phosphorus and Ca:P ratio varied between different groups from 6.02±0.35 to 9.63±0.78 g% (P-dl.05), 9.56±2.16to 28.94±4.05 mg% (P
Keywords: Biochemical profile; age; reproductive status; Holstein Friesian cattle; tropical climate